Human capital formation and tax evasion - Laszlo Goerke (Center for Economic Studies and ifo Institute (CESifo), 2012)
A strictly risk-averse individual with an exogenous gross income in period one can acquire human capital in the same period and evade taxes. Period-two income rises with educational investments in period one and can also be hidden from tax authorities. It is shown that a greater tax deductibility of educational investments and higher individual ability induce a positive correlation between tax evasion and educational investments in period two, whereas the relationship in period one is ambiguous. These theoretical predictions can explain diverse empirical findings on the correlation between education and tax evasion.
Keywords: H24; H26; I20; 330; human capital; income tax; tax evasion; Bildungsinvestition; Einkommensteuer; Steuerflucht; Theorie